2020
DOI: 10.1007/s10950-020-09963-y
|View full text |Cite
|
Sign up to set email alerts
|

Relation between ocean wave activity and wavefield of the ambient noise recorded in northern Poland

Abstract: The temporal and spatial variations of the wavefield of ambient noise recorded at ‘13 BB star’ array located in northern Poland were related to the activity of high, long-period ocean waves generated by strong storms in the Northern Indian Ocean, the Atlantic Ocean, and the Northern Pacific Ocean between 2013 and 2016. Once pre-processed, the raw noise records in time- and frequency-domains, and spectral analysis and high-resolution three-component beamforming techniques were applied to the broadband noise dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 68 publications
(131 reference statements)
0
4
0
Order By: Relevance
“…Recent advances in observational seismology studies analyzing the distribution and composition of the microseisms wavefield utilized seismic arrays across the globe using beamforming methods (e.g. Gal et al, 2015;Gerstoft et al, 2008;Landès et al, 2010;Lepore & Grad, 2020;Wang et al, 2021). It is widely acknowledged that coastal regions are the originating areas for PM (Ardhuin et al, 2015); however, the dominant source regions of SM vary in different parts of the world.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in observational seismology studies analyzing the distribution and composition of the microseisms wavefield utilized seismic arrays across the globe using beamforming methods (e.g. Gal et al, 2015;Gerstoft et al, 2008;Landès et al, 2010;Lepore & Grad, 2020;Wang et al, 2021). It is widely acknowledged that coastal regions are the originating areas for PM (Ardhuin et al, 2015); however, the dominant source regions of SM vary in different parts of the world.…”
Section: Introductionmentioning
confidence: 99%
“…Several approaches have been used to investigate the sources of seismic noise on a continental scale using either distant arrays distributed across Europe [Essen et al, 2003, Chevrot et al, 2007, Juretzek and Hadziioannou, 2016 or even seismic arrays on different continents [Friedrich et al, 1998, Stehly et al, 2006, Retailleau et al, 2017. Other studies have instead focused on the origin of the noise at specific networks and locations [Pedersen and Krüger, 2007, Beucler et al, 2015, Tanimoto et al, 2015, Craig et al, 2016, Lepore and Grad, 2020, Guerin et al, 2022.…”
Section: Introductionmentioning
confidence: 99%
“…Park & Miller, 2008; C. Park et al., 2004), spatial autocorrelation‐SPAC (Aki, 1965; Chávez‐García et al., 2006; Hayashi et al., 2022; Kita et al., 2011; Margaryan et al., 2009; Okada & Suto, 2003), multichannel analysis of passive surface waves‐MAPS (Chen et al., 2022; Cheng et al., 2016; Dai et al., 2021; Y. Liu et al., 2020; Mi et al., 2022; Pang et al., 2019; Zhou et al., 2018). In the past two decades, the ambient noise interferometry technique has been widely employed for subsurface structure imaging using ambient seismic energy from natural or anthropogenic sources (e.g., Lehujeur et al., 2016; Lepore & Grad, 2020; F.‐C. Lin et al., 2009; Martins et al., 2020; Nakata et al., 2011; Pan et al., 2016; Planès et al., 2020; Yao & van der Hilst, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al, 2020;Mi et al, 2022;Pang et al, 2019;Zhou et al, 2018). In the past two decades, the ambient noise interferometry technique has been widely employed for subsurface structure imaging using ambient seismic energy from natural or anthropogenic sources (e.g., Lehujeur et al, 2016;Lepore & Grad, 2020;F.-C. Lin et al, 2009;Martins et al, 2020;Nakata et al, 2011;Pan et al, 2016;Planès et al, 2020;Yao & van der Hilst, 2009). Campillo and Paul (2003) indicated that one can extract the empirical Green's function between two receivers by cross-correlating their ambient seismic noise recordings.…”
mentioning
confidence: 99%